Vitamin A deficiency in chronic cholestatic liver disease: Is vitamin A therapy beneficial? - Freund, Cora; Gotthardt, Daniel (Liver international, 2017)
Chronic cholestatic diseases are progressive diseases of the biliary tract that cause hepatic fibrosis and ultimately lead to liver failure. Liver transplantation is the sole curative option currently available, and because of high morbidity and mortality rates of these diseases, new therapeutic approaches are needed. Vitamin A is a nutrient essential for health as it regulates many processes, including epithelial growth and immunological processes. Vitamin A is primarily stored in hepatic stellate cells, and during liver injury, through an unknown mechanism, these cells lose vitamin A and convert into collagen-producing myofibroblasts, which contributes to hepatic fibrosis. Vitamin A deficiencies in chronic cholestatic diseases have been frequently reported, and therefore, retinoid metabolism has attracted a lot of attention. Retinoids have been shown to attenuate or even prevent hepatic fibrosis, and to regulate hepatic immunological response to cholestatic injury in different rodent models of chronic cholestasis. Recently, their potential as therapeutic drugs in primary sclerosing cholangitis patients was analyzed. The aim of this review is to summarize the existing knowledge and hypotheses about vitamin A role and the disease progression in cholestatic liver disease.
Gesehen am 04.05.2018